Implementasi Sistem Informasi Manajemen Pendidikan dalam Meningkatkan Kualitas Pendidikan : Literatur Review (Lembaga Pengembangan Kinerja Dosen, 2025)
The use of Education Management Information Systems (EMIS) can be an effective tool in achieving quality education. The purpose of this study is to understand how the implementation of Education Management Information Systems (EMIS) can improve the quality of education. This research adopts a literature review method. In the implementation of Education Management information Systems (EMIS) in various schools and colleges it is evident that the use of information technology contributes positively to improving the quality of education. Various applications such as SIMPATIKA, e-learning, fingerprint, and web applications have assisted in managing information, enhancing the karning process, measuring learning outcomes, and facilitating the enrollment of new students. However, the implementation process does not always proceed smoothly due to vurious supporting and inhibiting factors, Supporting factors, such as cooperation between parties and efforts to overcome obstacles, facilitate the smooth implementation of EMIS. On the other hand, technical challenges, human resource difficulties, and student challenges in following learning through applications are obstacles that need to be addressed.